Dynamic analysis of the arbitrary position of a particle robot around an inclined pipe based on virtual joints. (7th January 2020) - Liu, Dengbiao; Li, Cuiyun; Fan, Binghui; Zhong, Peisi
During the movement of a robot on the outside of a pipe, it either exhibits linear or rotating motion along the axis of the pipe. In this process, not only is there conversion between kinetic energy, potential energy, resistance power consumption, and external work, but there are also complex mechanical relationships that occur. To solve the dynamic problems of the out-pipe climbing robot in space, the axis and diameter of the pipe were simplified to the virtual joints of a robot with zero mass, and the virtual dynamic model of the robot in space has been established. According to the vector of the arbitrary position of a particle robot around an inclined pipe, combined with the improved Lagrange–Newton–Euler method, the system's dynamic equation that includes friction has been established, and the required driving force for an arbitrary position of the robot in the process of circling an inclined pipe has been obtained.